Pengaruh Kompetensi, Lingkungan Kerja dan Motivasi Berprestasi Terhadap Kinerja Pegawai Negeri Sipil Sekretariat Daerah Kota Padang - Mulia, Rizki Afri; Saputra, Nika (Jurnal Ilmiah Ekotrans & Erudisi, 2021)
This research aims to provide evidence that: 1) To determine the significance of the influence of employee competence on employee performance at the Padang City Regional Secretariat. 2) To determine the significance of the influence of the work environment on employee performance at the Padang City Regional Secretariat. 3) To determine the significance of the influence of achievement motivation on employee performance at the Padang City Regional Secretariat. 4) To determine the significance of the influence of competence, work environment, and achievement motivation on employee performance at the Padang City Regional Secretariat. Data collection was carried out using a survey method with a questionnaire for auditors. The data analysis technique used in this research is descriptive and quantitative analysis. The data collected is primary data which can be classified as independent variables and dependent variables. Competence, Work Environment, and Achievement Motivation (influence variables), and employee performance at the Padang City Regional Secretariat (influence variables). Hypothesis testing in this research uses multiple linear regression tests. Based on the research results, it is known that 1) competency has a positive effect on employee performance at the Padang City Regional Secretariat. Thus, hypothesis 1 is supported. 2) The work environment has a positive effect on employee performance at the Padang City Regional Secretariat. Thus, hypothesis 2 is supported. 3) Achievement motivation has a positive effect on employee performance at the Padang City Regional Secretariat. Thus, hypothesis 3 is supported. 4) Competence, work environment, and achievement motivation simultaneously influence employee performance at the Padang City Regional Secretariat. Thus, hypothesis 4 is supported.